A study of personality factors (Openness and Conscientiousness) and perceived level of career success in married individuals. - Kapure, Rajashree (International Journal of Scientific Research and Management (IJSRM), 2014)
In the present research study the researcher had conducted survey on married individuals in the age group of 25 to 50 yrs ,with respect to their personality factors and career success in their jobs or chosen profession. At a present scenario the world is becoming global but creating distances in the minds and lives of individuals. In the present life no one individual is away from identity crisis and that itself creating confusion in their work and family life. To analyze the data following objectives were framed. 1.To study the personality factors (openness and conscientiousness) amongst all the married individuals. 2.To study the level of career success amongst the married individuals. 3.To compare the difference between males and females with respect to their level of career success. For the present research in all 80 individuals were taken on the basis of purposive sampling method and the sample were collected from Nasik region. The inclusion criteria for the same was they should have minimum 05 years experience in their job/profession and they should be married and were in the age group of 25 to 50 yrs. To measure their score on openness and conscientiousness NEOFFI-S were used while the level of career success was measured with the help of self constructed scale of career success. Both the tests were rating scale type instruments containing good reliability and validity .Prior consent were taken from all the selected sample and approximately one hour time was required to complete both the tests. As per the data analysis with Pearson product moment correlation method the relationship between personalities dimensions such as openness and conscientiousness with career success of selected data were calculated. The level of career success in genders were compared with the help of‘t’ test. The present study confirms the role of personality factors in each individual’s career success and of course how at personal level identity crisis dominates individual’s professional life. Definitely the findings related with level of career success shows no gender difference. The researcher confirms the role of different factors such as one’s involvement in job professionalism, subjective aspects related with career success and number of years one completes in his/her profession dominates his/her level of career success.